Antioxidant Properties of Flaxseed Protein Hydrolysates: Influence of Hydrolytic Enzyme Concentration and Peptide Size. (27th April 2018) - Nwachukwu, Ifeanyi D.; Aluko, Rotimi E.
Abstract: Flaxseed is an emerging source of protein raw materials for bioactive protein hydrolysate production; however, there is insufficient information on the structural properties of its antioxidative peptides. The aim of this work was to determine the peptide composition and relationships to antioxidant properties of flaxseed protein hydrolysates (FPH) obtained using two protease (thermoase) concentrations (2.5 and 3.0%). The FPH were passed through ultrafiltration membranes to yield fractions with <1, 1–3, 3–5, and 5–10 kDa peptide sizes, which were also tested for antioxidant properties. Mass spectrometry data yielded several peptide sequences located within the flaxseed conlinin, but a lesser number was found in the 3.0% thermoase‐FPH. 2, 2‐Diphenyl‐1‐picrylhydrazyl radical scavenging was lowest (54%) for the 3.0% thermoase‐FPH while membrane separation enhanced the values up to 65% for the <1 kDa peptides. Metal chelation and iron‐reducing ability were also significantly ( P < 0.05) enhanced after membrane fractionation. In contrast, the hydroxyl radical scavenging ability was unchanged (2.5% thermoase‐FPH) or significantly ( P < 0.05) diminished (3.0% thermoase‐FPH) after membrane fractionation, except for the 5–10 kDa peptides that had notably ( P < 0.05) higher values. We conclude that the <1 and 1–3 kDa peptides may be useful agents to suppress oxidative stress within living tissues while the 3–5 and 5–10 kDa could be suitable preservatives to enhance food shelf life.